STRATEGY FOR IMPLEMENTING THE INDEPENDENT CURRICULUM IN ELEMENTARY AND MIDDLE SCHOOL EDUCATIONAL INSTITUTIONS IN WEST ACEH REGENCY - Rasyid, Suparta; Niswanto, Niswanto; Usman, Nasir Usman; Murniati, murniati AR; ismail, ismail; Bahrun, Bahrun (CV. Naskah Aceh, 2023)
The service aims to help school principals and teachers implement the independent curriculum in elementary school (ES) and junior high school (JHS) educational institutions in West Aceh Regency. The method used in this community service consists of 4 stages, namely; 1) preparatory phase; 2) implementation; 3) evaluation and monitoring; and 4) follow-up. The results of this service show an increase in knowledge and understanding regarding implementing the curriculum Merdeka. The impact resulting from this service is that teachers become more capable of implementing the curriculum Merdeka in the institutions they work in, and school principals can guide teachers who do not participate in this service to implement the curriculum Merdeka in the learning process.